Rancangan dan Pembuatan Alat untuk Mengambil Air Suci Secara Otomatis Menggunakan Arduino Uno - Abisha, Vinsensius Levin Setya; Prihatmajaya, Putu Samuel; Candrasari, Diwahana Mutiara; Manurung, Ria (Joined Journal (Journal of Informatics Education), 2022)
The existence of covid-19 has forced the government to implement health protocols. By implementing this, the procedure for celebrating the Eucharist is taking holy water to make the sign of the cross when entering and leaving the church temporarily. Covid-19 makes the use of goods or other things that are used simultaneously considered less hygienic. The implementation of health protocols carried out by the government includes washing hands, using hand sanitizer and using masks. The holy water used together is not optimal in terms of cleanliness, so with the implementation of the health protocol, this procedure has been temporarily suspended until now. At this time technology is developing very rapidly so with technology Catholic church people can get holy water without having to use it simultaneously by utilizing embedded system technology. This study aims to enable Catholic church members to get holy water according to health protocols. This tool for taking holy water automatically is designed and made so that it can accommodate people to return to carrying out the procedure for celebrating the Eucharist by making the sign of the cross using holy water. This research is expected to provide benefits, namely being able to accommodate people to get holy water to make the sign of the cross in accordance with health protocols. The result of this research is an automation system in the form of a tool to take holy water automatically using Arduino Uno R3 as the microcontroller.